Effect of pH, Temperature and Medium Composition on Xylanase Production by Bacillus sp. AQ-1 and Partial Characterization of the Crude Enzyme - BUDIASIH WAHYUNTARI; NISA RACHMANIA MUBARIK; SISWA SETYAHADI (Microbiology Indonesia, 2009)
Bacillus sp. AQ-1 was isolated from household aquarium sediment. The isolate produced extracellular xylanolytic enzymes on xylan containing agar medium. Based on morphological, and physiological analysis, the isolate was identified as Bacillus sp. AQ1. The effect of temperature and pH on isolate growth and xylanase production were observed. The best condition observed for the enzyme production in Luria Broth supplemented with 0.5% oat spelt xylan medium was at 40 °C pH 7. The maximum enzyme production was 0.23 U mL-1 after 20 h of fermentation. Two different medium compositions (A and B) were examined for xylanase production. The maximum growth of the isolate and the xylanase production was better in A medium. Replacing oat spelt xylan in medium A with fruitless oil palm bunch in the medium caused the growth slightly slower than that of in the original formula. However, the xylanase production was 3 times higher in fruitless oil palm bunch medium. Optimum activity of the crude enzyme was observed at 60 °C and pH 7. Each ml of the crude enzyme contained 55.21 U xylanase, 8.12 U amylase and 0.50 U carboxymethylcellulase